Relationship between weapon size and six key behavioural and physiological traits in males of the European earwig - Blackwell, Samantha E M; Pasquier, Laura; Dupont, Simon; devers, Severine; Lecureuil, Charlotte; Meunier, Joël (Peer Community Journal)

(untitled)
In many animals, male weapons are large and extravagant morphological structures that typically enhance fighting ability and reproductive success. It is generally assumed that growing and carrying large weapons is costly, thus only males in the best condition can afford it. In the European earwig, males carry weapons in the form of forceps-like cerci, which can vary widely in size within populations. While long forceps appear to increase male’s access to females, it is unknown whether it also correlates with other important male life-history traits. This information is important, however, in determining the potential reliability of forceps length as an indicator of male quality and the stability of this signalling system. Here, we tested whether forceps length is associated with six important behavioural and physiological traits in males of the European earwig. We sampled hundreds of males from two populations, selected 60 males with the longest and shortest forceps from each population, and then measured locomotor performance, boldness, aggregation behaviour, survival under harsh conditions, sperm storage, and survival after pathogen exposure. Contrary to our predictions, we detected no main association between forceps length and the traits measured. This lack of association was consistent between the two populations, although there were population-specific levels of boldness, aggregation and survival in harsh conditions (for long-forceps males only). Overall, these results challenge our current understanding of the function and quality signal of forceps length in this species and raise questions about the evolutionary drivers that could explain the maintenance of weapon size diversity within and between populations.